JOHN MINOS TZANAKAKIS Obituary: PROFESSOR JOHN MINOS TZANAKAKIS, 1927-2025 - Economopoulos, Aristeidis (ENTOMOLOGIA HELLENICA, 2025)
An exceptional entomologist, a rare personality Born in Thessaloniki (Macedonia) in January 1927. His father originated from Western Crete (village Elos, Kissamos province), while his mother from Constantinople (Istanbul). During his early years of high school (World War II, German occupation period) he lived in Kissamos, where, among others, he was cultivating vegetables to feed his family. This agricultural activity marked out his inclination to agriculture and in particular plant protection. Thereafter, his successive main steps were: Agricultural University of Athens (then Highest Agricultural School of Athens) 1945-1950, Shell Company (Hellas) (plant pest control) 1953-1955, University of California at Berkeley Department of Entomology Ph.D. 1955-1959, Laboratory of Entomology at the “Democritus” Nuclear Research Center Athens-Greece founder and head 1963-1969, Professor of Applied Zoology and Parasitology at the Department of Agriculture and Forestry of Aristotle University of Thessaloniki 1969-1995. From Berkeley he received several letters of recommendation, all praising his integrity and extraordinary achievements in his graduate work. As an example, Professor D. D. Jensen, then advisor of graduate students, concludes: “I consider him as one of our 3 best graduate students among over 60 enrolled at present in Entomology”.